Spectral properties of power graph of dihedral groups - Romdhini, Mamika Ujianita; Nawawi, Athirah; Al-Sharqi, Faisal; Al-Quran, Ashraf (New York Business Global, 2024)
This paper focuses on the power graph of dihedral groups of order 2n, D2n, where n ≥ 3. We show the characteristic polynomial of the power graph corresponding to the adjacency, Laplacian, signless Laplacian, and normalized form of these matrices.